The ripple effect of strain in times of change: how manager emotional exhaustion affects team psychological safety and readiness to change - Groulx, Patrick; Maisonneuve, Francis; Harvey, Jean-François; Johnson, Kevin J. (Frontiers in Psychology, 2024)
Introduction: Managers assume a pivotal role during periods of organizational change, yet there exists a notable gap in our understanding of how their emotional exhaustion may impact their capacity to generate readiness to change within their teams. Grounded in the Conservation of Resources Theory (COR), this study explores the crossover effect of managers' emotional exhaustion on team readiness to change. We expect this to occur through higher levels of laissez-faire leadership, which impacts the teams' psychological safety. Methodology: Data was gathered within a Canadian governmental organization undergoing two significant changes-cultural change and digitalization-with a specific focus on leadership as a pivotal factor in preparing teams for change. Employing surveys from 372 team members and 62 managers affected by this change, we conducted path analysis to empirically test the proposed model across 74 teams and their respective managers.Data was collected in a Canadian governmental organization undergoing a major transformation. Leadership was studied as a key lever on making teams ready to change. Using team members and manager survey, we used path analysis to test the proposed model with 74 teams and their manager. Results: Managers' emotional exhaustion has a negative indirect effect on team readiness to change. The double mediation pathway implies a direct relationship on higher laissez-faire leadership, which is predicting lower levels of psychological safety. In turn, psychological safety is linked to higher team readiness to change. Conclusion: Managers must invest significant resources to fulfill their roles and responsibilities during strategic change. Managers who feel exhausted during change may look for ways to protect some of their resources by reducing the time and energy they invest leading their team. This self-preserving resource strategy has detrimental consequences on teams' effectiveness during change due to an indirect crossover effect that affects the levels of psychological safety on the team.